Microwave-Activated Biomass-Derived Carbon for Smart Sensor Applications in Pollutant Detection and Drinking Water Purification - Subagio, Agus; Qudsiyah, Risma Aimatul; Taufiq, Heydar Ruffa; Umiati, Ngurah Ayu Ketut; Hamidah, Ida; Nurrudin, Ahmad; Rusydi, Andriyo (Trends in Sciences, 2026)
The increasing demand for sustainable materials in environmental monitoring has encouraged the use of biomass waste for the development of advanced sensor technology and water purification. This study reports the synthesis of activated carbon (AC) from tea stem biomass through activation with a microwave at 800 W for 120, 180, and 240 s. The variation in time was used to investigate the effect of activation time on structure, porosity, and electrochemical performance. X-ray diffraction confirmed a progressive transition from predominantly amorphous carbon at 120 s to a more regular graphite structure at 180 - 240 s. AC Tea Waste 180 s showed a balanced degree of crystallinity without significant structural fragmentation. SEM analysis showed that 180 s of activation resulted in a highly open and interconnected pore network, while shorter activation resulted in relatively closed pores, and longer activation caused surface cracks and particle fragmentation. Electrochemical testing in a 1 M Na₂SO₄ solution using a three-electrode configuration showed that AC activated for 180 s produced the highest specific capacitance of 735.76 F g⁻¹ at a current of 2.5 A g⁻¹, accompanied by better rate capability and lower charge transfer resistance compared to the 120- and 240- s samples. At the same activation time, the material achieved an energy density of 366.41 Ws g⁻¹ at a power density of 0.875 W g⁻¹, demonstrating a balance between energy and power for practical applications. The optimized AC exhibits a characteristic quasi-rectangular cyclic voltammetry profile of electrochemical double-layer capacitance, stable charge-discharge behavior, and favorable ion transport, confirming its suitability as a supercapacitor transducer layer. Furthermore, the high carbon purity and tailored pore structure of the 180 s sample provide strong sensitivity for pollutant detection and robust adsorption capacity for drinking water purification, demonstrating that tea stalk waste is a low-cost, renewable raw material for multifunctional smart sensors and clean water technology. HIGHLIGHTS Microwave-assisted activation produced porous bio-carbon from tea stem waste. Optimal 180 s activation achieved 735.76 F g⁻¹ specific capacitance at 2.5 A g⁻¹. Enhanced pore structure and crystallinity with minimized energy consumption. Strong pollutant sensitivity and high adsorption capacity in water purification. Dual-function material enabling smart sensor and clean water integration. GRAPHICAL ABSTRACT